Novos caminhos para qualificar a ação missionária na Igreja Evangélica de Confissão Luterana no Brasil - Conrad, Débora Raquel Klesener (2013)
The current work intends to present the trajectory of the IECLB Missionary Plan of Action (IMPA) The IMPA offers impulses for theological reflection on the Church's missionary action, as well as presents a methodological proposal for the realization of strategic planning. The IMPA came out as an element of unity, in a transition period between a centralized organizational structure, to a decentralized structure. Its trajectory has been set by two steps that presented different emphases and approaches, however, kept the focus on missionary action. To guide the reflection and implementation process of the IMPA in different instances, theorics subsidies were elaborated. Even with several initiatives, reports of few Synods point to difficulties in the appropriation of the methodology proposed for the realization of strategic planning and consequently, its effectuation. However, there are also reports quite positive in relation to the results of the process of realizing the planning. The strategic planning is not something dissociated of Community management, but needs to be incorporated to the management process. The IMPA propitiated the awakening of the Church for a missionary action more articulated, as well as may have opened paths for reflection about the management model in the Church.